ANALISIS PERPINDAHAN PANAS DAN MASSA PADA PENGERINGAN BUAH SALAK, NANAS, DAN PEPAYA MENGGUNAKAN PENGERING KABINET DENGAN PERLAKUAN DEHIDRASI OSMOTIK - , FATIKA ANISA ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The objective of this research was to determine the kinetic of drying on sliced fruit with various pretreatments.The cabinet dryer with electric heater was used in this research. The drying temperatures were 50oC, 60oC, and 70oC. The sliced of pineapple, papaya, and snake fruit were used as samples. Blanching process and sugar solution dipping were used for all variations. Citric acid and sodium metabisulphite dipping, citric acid, sodium metabisulphite, and calcium chloride dipping, citric acid only dipping, and citric acid and calsium chloride dipping were noted as S1, S2, S3, and S4 variations respectively. One controlled variation was noted as S0 which was fruit that was not given the pretreatments variation. The result showed that the osmotic dehydration had effect on reducing the moisture content of snake fruit, pineapple, and papaya for 10 â 13%, 11 â 18%, and 10 â 16% respectively. The time needed for drying fruit process at 50oC, 60oC, and 70oC was 24 hour, 15 â 16 hour, and 12 â 13 hour respectively. The drying rates in dry basis analysis at constant period of snake fruit, pineapple, and papaya were 23,97%/hour â 74,20%/hour, 28,85%/hour â 143,07%/hour, and 38,34%/hour â 143,84%/hour respectively, while the drying rates at falling period were 0,19/hour â 0,65/hour, 0,16/hour â 0,52/hour, and 0,22/hour â 0,65/hour respectively. The coefficients of convective heat transfer of snake fruit, pineapple, and papaya were 0,15 W/(m2.oC) - 3,32 W/(m2.oC), 0,08 W/(m2.oC) - 1,65 W/(m2.oC), and 0,003 W/(m2.oC) - 2,33 W/(m2.oC) respectively. The activation energies of snake fruit, pineapple, and papaya were 23,95 kJ/mole â 28,91 kJ/mole, 20,29 kJ/mole â 27,92 kJ/mole, and 6,66 kJ/mole â 27,71 kJ/mole respectively at constant period and 39,63 kJ/mole â 56,38 kJ/mole, 39,23 kJ/mole â 45,89 kJ/mole, and 27,82 kJ/mole â 47,23 kJ/mole respectively at falling period. The dipping on osmotic solution process for the fruit had effect on reducing drying rate. The using of calsium chloride had no significant effect to the quality of dried fruit. The using of sodium metabisulphite had only effected the color of snakefruit significantly to prevent browning process while it hadnât effected the color of pineapple and papaya significantly. The fruit drying process using cabinet dryer gave the best result and produced the dried fruit that many people liked if the fruits were dried at 50oC for drying temperature and before they put on the dryer, theyâre dipped on sodium metabisulphite and citric acid solution, given the blanching treatment, and dipped on sucrose solution (sugar solution).